Capitalising of agricultural support in higher land price - Svenungsson, Gustaf (2019)
This thesis aims to investigate to which extent EU: s decoupled direct payments to farmers capitalise in higher prices of agricultural land during 20032016 and how the capitalisation degree changes at the same time. To do so, it combines the traditional net present method with a hedonic pricing model, in order to evaluate the capitalising degree of different agricultural support forms. Quantile, OLS and panel data regressions are used to determine the correlation between the explanatory variables and the dependent variable (the price of agricultural land). The used explanatory variables are supposed to capture how the structure and profitability of the agricultural sector, localisation of the agricultural land, agricultural support and demand of agricultural land for other usage than agriculture influence the price of agricultural land.